ETHNOBOTANICAL INVESTIGATION OF TRADITIONAL NATURAL DYES (CASE STUDY: MARKAZI PROVINCE OF IRAN) - MARYAM MOBARAKI MOGHADDAM; MOHAMMAD AZADBAKHT; MASOUD AZADBAKHT (International Journal of Pharma and Bio Sciences, 2016)
Ethnobotany is study of human behavior in a particular culture and of the use of local plants. Ethnobotanical studies have drawn increasing attentions in the food and drug industry. Therefore, the present study aimed to investigate ethnobotany of the traditional natural dyes in Markazi Province of Iran. The study included volunteer factories, groceries (medicinal herbs sellers), and lower class people in the province. Data were collected using a questionnaire, and then analyzed using SPSS version 20 software. Results showed that 26.6% of the groceries and 75% of the people obtained dyes of natural sources. Leaves, fruit, stems, flowers, seed, roots, bark and rhizome were the most preferred parts of the plants for production of the dyes, respectively. Boiling of plants were dominant approach among the groceries and soaking was among people and factories for the production of dyes. Plants dyes were mostly used for foods among the people, for hair coloring in the groceries, and for production of antiseptic mouthwashes in the factories. Henna and saffron have been most used to produce color by people and groceries. It seems that use of natural dyes is more prevalent in the groceries in Markazi province of Iran, while the people and factories are less interested in these dyes.